IMPLEMENTATION OF APPLE ACIDIFIER IN CANNED CUCUMBERS PRODUCTION - DIANA CRUCIRESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The present study analyzes the acidifier from thinned unripe apples, in order to obtain a source of natural acidity. The technological scheme for obtaining the natural acidifier was developed, which was characterized by high acidity (2.21 ± 0.1 %) and significant amount of total soluble solids (7.93 ± 0.2 %). The contents of organic acids and carbohydrates were analyzed. The main organic acid was malic acid with 26.43 ± 0.003 g·dm-3, and the main carbohydrate was fructose with an amount of 35.17 ± 0.095 g·dm-3, glucose being 2 times less. The acidifier has been proposed as an alternative to acetic acid in the preservation of cucumbers (Cucumis sativus). Thus, 2 series of experimental samples were produced, using the substitution of 50 % (PA50) and 100 % (PA100) of acetic acid with apple acidifier, compared to the control sample (according to the classic recipe). All samples were characterized physico-chemically and subjected to organoleptic evaluation. The developed products showed very good results compared to the control. However, the most relevant and valuable was the PA100, having the best quality indices. The production and use of apple acidifier allows the efficient utilization of raw materials by increasing sustainability of horticultural sector and leads to obtaining healthy and ecological products.